2014
DOI: 10.2147/copd.s70257
|View full text |Cite
|
Sign up to set email alerts
|

How do COPD comorbidities affect ICU outcomes?

Abstract: Background and aimChronic obstructive pulmonary disease (COPD) patients with acute respiratory failure (ARF) frequently require admission to the intensive care unit (ICU) for application of mechanical ventilation (MV). We aimed to determine whether comorbidities and clinical variables present at ICU admission are predictive of ICU mortality.MethodsA retrospective, observational cohort study was performed in a tertiary teaching hospital’s respiratory ICU using data collected between January 2008 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
6
15
1
1
Order By: Relevance
“…Factors indicating a poor prognosis for COPD subjects in the ICU are the need for IMV, presence of pneumonia, cachexia, coronary artery diseases, arrhythmia, hypertension, and higher APACHE II scores. 31 Mortality risk factors in the present study were found to be similar: the need for IMV, the presence of arrhythmia as a comorbidity, the presence of septic shock and a resistant pathogen infection, CRP values ≥50 mg/mL, and an NLR ≥16 on admission to the ICU. A meta-analysis that included 979 COPD subjects from 14 studies found that COPD subjects had an average of 35% intubation for IMV and a mean mortality rate of 45%.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Factors indicating a poor prognosis for COPD subjects in the ICU are the need for IMV, presence of pneumonia, cachexia, coronary artery diseases, arrhythmia, hypertension, and higher APACHE II scores. 31 Mortality risk factors in the present study were found to be similar: the need for IMV, the presence of arrhythmia as a comorbidity, the presence of septic shock and a resistant pathogen infection, CRP values ≥50 mg/mL, and an NLR ≥16 on admission to the ICU. A meta-analysis that included 979 COPD subjects from 14 studies found that COPD subjects had an average of 35% intubation for IMV and a mean mortality rate of 45%.…”
Section: Discussionsupporting
confidence: 61%
“…A previously published study investigating the outcomes of ARF subjects with COPD requiring ICU admission from 2008 to 2012 (n=1,013) showed a 16.9% mortality rate. 31 Mortality in 698 subjects with COPD exacerbations of infectious origin was 21.6%; however, COPD subjects with pneumonia (n=241) had a higher rate of mortality (39%). Factors indicating a poor prognosis for COPD subjects in the ICU are the need for IMV, presence of pneumonia, cachexia, coronary artery diseases, arrhythmia, hypertension, and higher APACHE II scores.…”
Section: Discussionmentioning
confidence: 96%
“…Third, other co morbidity as chronic renal failure or neurologic conditions influence by hypercapnic could difficult interaction of modafinil as coincident psychiatric drugs like antidepressive or anxiolytic, that in some cases are associated in chronic respiratory insufficiency. 4 6 Additionally, coexistence of COPD and sleep breathing disorders determinate more complexity in this prescription. 7 , 8 …”
mentioning
confidence: 99%
“…This finding is in accordance with those reported by Teixeira et al They observed that patients with history of COPD had a high mortality rate in ICU (27%) and two years after hospital discharge (68%) 24 . Ongel et al recommend that cases with severe COPD and cardiac comorbidities might be carefully monitored in intensive care settings because of the elevated risk of mortality 25 .…”
Section: Discussionmentioning
confidence: 99%